Pengaruh Konflik Peran, Kompetensi, dan Motivasi Pegawai Terhadap Kinerja Pegawai Inspektorat Kota Denpasar - Suaryana, I Gusti Ngurah Agung; Noviari, Naniek (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No.1, Februari 2018 (pp. 1-144)DO - 10.24843/JEKT.2018.v11.i01.p06, 2018)
The role of the Regional Inspectorate becomes more important as the body charged with the supervision and development in the region. This stimulates more research on factors that affect the performance of the inspectorate. Factors suspected to be the determinants of the performance of the regulatory regions, namely conflict role, competence, and motivation. The population of this study is as well as a sample of the research, is inspectorate employees on government of Denpasar who directly involved in the supervision and guidance of preparation of financial statements of every SKPD in Denpasar. The research instrument is in the form of questionnaires. The analysis used is partial least square. This study found out that the competence and motivation affects employee performance inspectorate. Role conflict was not shown to affect the performance of the inspectorate. The results of this study are expected to help the leader of the agency Inspectorate in making decisions concerning training, assignments, and employee motivation given to the environment Inspectorate Denpasar.
Keywords: conflict of roles, competencies, motivation, and performance.